Assessing the Relationship between Psychosocial Learning Environment and Higher Order Thinking Skills / Mohd Azry Abdul Malik ...[et al.] - Abdul Malik, Mohd Azry; Adnan, Mazlini; Abdul Rahman, Amri; Mohd Noor, Mohd Rahimie; Mayidin, Mohd Baharim (Unit Penerbitan UiTM Kelantan, 2016)
The aimof this studyisto investigate the influence oflearning environment (psychosocial) on higher order thinking skills ability among higher education students.A total of 164 undergraduate chemistry studentsin UniversitiTeknologi Malaysia (UTM)were selected as sample usingdisproportionate stratified sampling technique. The study instruments wereadapted from College and Classroom Environment Inventory CCEI, and Marzano Higher Order Thinking Dimension of Learning. Multiple linear regression analysis indicatesthat psychosocial learning environment constructs have a significant direct effect onHOTS; Student-Student Relationship (ß=0.395), Attitudes toward Students (ß=0.344), Class Organization (ß=0.161), Autonomy and Power Sharing (ß=0.076),and StudentsInterest and Motivation (ß=0.176). Moreover, Tukey’s test shows thattheperception towards HOTS has a significant difference among differentstudents’ achievement (CGPA)